Losses, Gains, and Changes to the Food Environment in a Rural Kentucky County during the COVID-19 Pandemic - Makenzie L. Barr (MDPI AG, 2021)
The COVID-19 pandemic has caused alterations to be made in the way many people access, prepare, and consume food. Rural communities are particularly impacted due to pre-existing structural vulnerabilities, i.e., poverty, lack of infrastructure, and limited fresh food options. This study aimed to characterize experiences of one rural Appalachian community’s changes to the food environment during the pandemic. In April 2021, six focus groups were conducted with residents of Laurel County, Kentucky. Using grounded theory, we identified losses, gains, and overall changes to the community food environment since the onset of COVID-19. Seventeen Laurel Countians (17 female; ages 30–74) participated in the six focus groups. Three main themes emerged regarding food environment changes—(1) modifications of community food and nutrition resources, (2) expansion and utilization of online food ordering, and (3) implications of the home food environment. Rural communities faced considerable challenges during the COVID-19 pandemic, in part, due to gaps in existing infrastructure and loss of pre-existing resources. This study illustrates the complexity of changes occurring during COVID-19. Using the preliminary data obtained, we can better understand pre-existing issues in Laurel County and suggestions for future programming to address the inequitable access and response during public health emergencies and beyond.